The miniseries Stateless: fiction and reality about the refugee condition - Carvalho, Marcus Vinicius de Souza Perez de [UNESP] (2023)
This essay presents a reflection on the refugee's condition of existence, his reasons, the process of displacement and the violence suffered along his trajectory from the audiovisual miniseries Stateless (2020). The stories of refugees from a migrant detention camp told in the miniseries were inspired by real cases that were widely reported by the international media and the discussion on migration policy. This essay exposes three central cores that discuss the content of the miniseries in the light of the contemporary debate on migration and the refugee crisis, the first represented by the character Sofie and which is based on the story of Australian citizen Cornelia Rau, the second lived by the migrant Ameer and his Afghan family and the third formed by Cameron, the security guard at the refugee detention camp.